Formation potential of disinfection by products of 4 water sources after Nanofiltration (NF) and Advanced Oxidation Processes (AOPs) at optimal and sub-optimal conditions - Losty, Erin; Goslan, Emma H. (Cranfield University, 2017)
The importance of understanding the impact of different precursor removal treatments on disinfection byproducts (DBP) formation concentrations. This can be elucidated by exploiting the physico-chemical characteristics of NOM in raw water source groups to minimise the formation of DBPs.. Pre-curser technology treatments include coagulation, Ion exchange, Adsorption, membranes biotreatment, ozone and AOPs. Establishing correlations experimentally between different raw water sources, water treatment used and DBP formation, by measuring raw water characteristics at the point before treatment and DBP-FP in the corresponding final water just after treatment using the analytical methods as above and the previously established methods for HAA and THM analysis. Analytical methods for the determination of DBPs from 16 categories are used to determine an extensive range of DBPs, giving a better understanding of the composition of the DBP mixture as a whole. The analytical methods can then be used to determine and compare water treatment technologies under optimal and suboptimal conditions and hence provide operational advice on minimising DBP formation by comparing treatment methods.
Keywords: Disinfection byproducts; Nanofiltration; Advanced Oxidation Processes